Pengaruh sikap dan nilai Islam terhadap niat untuk menghadiri program bahasa Inggeris di masjid / Muhammad Saiful Anuar Yusoff ... [et al.] - Yusoff, Muhammad Saiful Anuar; Che Hassan, Nor Syamimi Iliani; Mohammad Nor, Nor Hairunnisa; Yusof, Nabihah (2018)
The introduction of English language programs at mosque is meant to enhance English proficiency among Muslims. The purpose of this study is to examine students' perceptions of their willingness to attend English language programs at mosques. Attitudes and subjective values of Islamic religion are assumed to influence individuals’ intentions and encourage them to attend English language programs held at mosques. The influence of these two variables on students’ willingness to attend the programs is reviewed. A total of 160 data were obtained from respondents who attended the January-March 2018 interim session. Students from five different faculties in Universiti Teknologi MARA Kelantan participated in this study. SmartPLS 3 was used to run the analysis. The result of the study revealed that attitude did not have influence on students' intention to attend English language programs at mosques. Meanwhile the subjective value of Islamic religion positively affected the respondents' intention to attend the programs. The findings provide a useful point of view in exposing affective components that encourage students to attend mosque-based English language programs. The findings suggest that the importance of English language from the religious point of view should be emphasized to motivate students to attend English language programs.